Modification of dolomites using tin and zinc as efficient solid catalysts for methyl esters production - Zdainal Abidin, Shajaratun Nur (2014)
Rapid energy consumption nowadays has led to the development of renewable resources of energy such as biodiesel. However, high cost of biodiesel production retards further development of this industry. Dolomite is a naturally occurring source of CaO and MgO which promotes a high potential heterogeneous base catalyst for biodiesel production. Transesterification of palm oil via calcined dolomite (AD8) catalyst exhibited 98.3 % conversion of fatty acid methyl ester (FAME). Selective metal oxides, Sn and Zn were as dopants since they have amphoteric properties which can improve the basicity of the parent material (dolomite). In order to obtain modified dolomite catalyst, 1, 3 and 5 % of metal oxides (Sn and Zn) were doped separately on the AD8 via wet impregnation method and exposed for calcination in air at 773 K for 3 h. These catalysts were denoted as 1DSN, 3DSN and 5DSN for Sn-dopant, whereas 1DZN, 3DZN and 5DZN for Zndopant. The catalysts were characterized by using X-ray Diffractometer (XRD), Brunauer-Emmet-Teller (BET) surface area, Scanning Electron Microscopy (SEM) and Temperature Programmed Desorption (TPD) of CO2. The catalysts were then employed for transesterification reaction under different conditions (time of reaction, methanol to oil molar ratio and amount of catalyst) to investigate the catalytic activities of the catalysts. From the result, calcined dolomite (AD8) which has been doped with 3 % of SnO2 (3DSN) showed optimum conversion of 99.98 % at the least conditions i.e. 1 wt.% of catalyst amount, in 15:1 methanol to oil molar ratio reacted in 4 h compared to 3DZN and AD8. The catalytic activities of these catalysts were found depending on the basicity and the surface area of the catalyst used. Several tests were conducted to study the physicochemical properties such as pour point, flash point, kinematic viscosity, sulphur content and cloud point of biodiesel produced. Based on the results, the synthesized biodiesel is comparable with conventional diesel in the market since it meets the international standards of biodiesel (ASTM, EN) and MS for diesel fuel specifications as well.